Photosynthetic, Biochemical and Enzymatic Investigation of Azolla microphylla in Response to an Insecticide-Hexachlorohexahydro-Methano-Benzodioxathiepine-Oxide - Raja, Waseem; Rathau, Preeti; John, Suchit A.; Ramteke, P.W. (Our Nature, 2013)
A study on the heterocystous, nitrogen fixing Water fern, Azolla microphylla was carried out to investigate the effect of an organochlorine insecticide (hexachloro-hexahydro-methano benzodioxathiepine-oxide, called as endosulfan) at different concentrations of 0, 50, 100, 200, 400 and 600 ppm on fresh weight, dry weight, photosynthetic pigments, stress metabolites such as ascorbic acid, proteins, and nitrogen metabolism activity like nitrate reductase and nitrate uptake. The inhibition was found to be dose dependent. The insecticide endosulfan showed to be deleteriously affecting the activities in the Azolla microphylla. Endosulfan adversely depleted the cellular activities, leading to a marked increase in the Vitamin-C at lower concentration and gradually decreases at higher concentrations. Decrease in protein was clear and activities like nitrate reductase and nitrate uptake also increases up to certain concentration and at higher concentration slightly decreases. Despite of deleterious effects of endosulfan on the Azolla microphylla, a unique regenerating ability in presence of the insecticide was observed by the end of five days in the lower doses of insecticide. Azolla seems to help sustain the soil nitrogen supply by returning nitrogen to quantities roughly equal to those extracted from the soil by the rice plant. DOI: http://dx.doi.org/10.3126/on.v10i1.7775